Sedentary behaviour and disease risk - Joseph Henson; Marieke De Craemer; Thomas Yates (BMC, 2023)
Abstract Sedentary behaviour has become the new reference of living, which has paralleled the increase in the prevalence of multiple chronic diseases. Here, we highlight the evidence to date and propose specific topics of interest for the Collection at BMC Public Health, titled "Sedentary behaviour and disease risk".